Gasoline - Campany, David (London : Mack, 2013)
The gas station is one of the most iconic of twentieth century buildings. Recognised across the world, it is arguably most established on American soil where the notion of the road trip on a full tank of gas is culturally ingrained. Gasoline presents 35 archive press images of gas stations taken between 1944 and 1995. Gasoline can be read as a cautionary tale about the modern dependence on oil, about news photography, about the shift from film to digital imaging, or as a minor history of car design and vernacular architecture. Marked with the grease pen notations of the newspapers art directors, the photos tell of oil shortages, road congestion, crimes, accidents and choking cities.
boek
Keywords: Campany, David